2003
DOI: 10.1093/condor/105.3.567
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Hydrogen Stable-Isotope Ratios Between Adult and Nestling Cooper's Hawks

Abstract: Hydrogen stable-isotope analysis of feathers is an increasingly popular method for estimating the origins of migrating and wintering birds. Use of this method requires that investigators know which feathers are grown on breeding grounds and how the hydrogen stable-isotope ratios of feathers (δDf) relate to those of local precipitation (δDp). In this study, we measured δDf of adult (primaries 1, 3, and 10) and nestling Cooper's Hawks (Accipiter cooperii) in Wisconsin, North Dakota, and British Columbia, Canada.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
31
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 19 publications
5
31
0
1
Order By: Relevance
“…Similar to several other studies, we found that SY individuals had more depleted δ 2 H f values compared to ASY individuals (Meehan et al 2003;Langin et al 2007;Gow et al 2012;Haché et al 2012). Explanations for this variation include differences in physiology and diet between the age classes (Hobson et al 1999;Meehan et al 2003).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Similar to several other studies, we found that SY individuals had more depleted δ 2 H f values compared to ASY individuals (Meehan et al 2003;Langin et al 2007;Gow et al 2012;Haché et al 2012). Explanations for this variation include differences in physiology and diet between the age classes (Hobson et al 1999;Meehan et al 2003).…”
Section: Discussionsupporting
confidence: 89%
“…Similar to several other studies, we found that SY individuals had more depleted δ 2 H f values compared to ASY individuals (Meehan et al 2003;Langin et al 2007;Gow et al 2012;Haché et al 2012). Explanations for this variation include differences in physiology and diet between the age classes (Hobson et al 1999;Meehan et al 2003). Differences in δ 2 H values of prey items and drinking water and/or differences in the proportion of those items consumed among age classes may lead to systematic variation in δ 2 H f values between younger and older individuals (Langin et al 2007;Betini et al 2009).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Factors other than precipitation may also exert an influence on δ 2 H values of bird blood at breeding sites. High temperatures can increase evaporative water loss, thus increasing δ 2 H tissue values of nestlings, as suggested in studies of Cooper's Hawks ( Accipiter cooperi ; Meehan et al 2003) and nestling Tree Swallows ( Tachycineta bicolor; Betini et al 2009). If present, these effects are unlikely to have had large influence on the δ 2 H blood values of Bicknell's and Swainson's thrushes at their breeding sites.…”
Section: Discussionmentioning
confidence: 88%